Metabolic Alternations During Gestation in Dezhou Donkeys and the Link to the Gut Microbiota - Li, Yan; Ma, Qingshan; Liu, Guiqin; Zhang, Zhenwei; Zhan, Yandong; Zhu, Mingxia; Wang, Changfa (Frontiers in Microbiology, 2022)
The maternal intestinal microbial community changes dramatically during pregnancy and plays an important role in animal growth, metabolism, immunity and reproduction. However, our understanding of microbiota compositional dynamics during the whole pregnancy period in donkey is incomplete. This study was carried out to evaluate gut microbiota alterations as well as the correlation with serum biochemical indices, comparing pregnant donkeys to nonpregnant donkeys. A total of 18 pregnant (including EP, early-stage pregnancy; MP, middle-stage pregnancy and LP, late-stage pregnancy) and 6 nonpregnant (C as a control) donkey blood samples and rectum contents were collected. The results showed that pregnant donkeys had higher microbial richness than nonpregnant donkeys and that the lowest microbial diversity occurred at the EP period. Moreover, the relative abundances of the families Clostridiaceae and Streptococcaceae were significantly higher in the EP group (p < 0.05) than that in the C and MP groups, while the relative abundances of the families Lachnospiraceae and Rikenellaceae were significantly lower in the EP group (p < 0.05) than that in the C group. The predicted microbial gene functions related to the inflammatory response and apoptosis, such as Staphylococcus aureus infection, the RIG-1-like receptor signaling pathway and apoptosis, were mainly enriched in EP. Furthermore, pregnant donkeys had higher glucose levels than nonpregnant donkeys, especially at EP period. EP donkeys had lower triglyceride, total protein and albumin levels but higher malondialdehyde, interleukin 1β, interleukin 6 and tumor necrosis factor-α levels than those in the C and MP groups. Additionally, there were strong correlations between inflammatory cytokine levels and the relative abundances of genera belonging to the Clostridiaceae and Streptococcaceae families. This is the first comparative study performed in donkeys that indicates that pregnancy status (especially in the early pregnancy period) alters the gut microbiota composition, which was correlated with serum biochemical parameters. These results could provide useful information for improving the reproductive management in Dezhou donkeys.